The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1002/ece3.333
|View full text |Cite|
|
Sign up to set email alerts
|

Effects ofCO2enrichment on photosynthesis, growth, and nitrogen metabolism of the seagrassZostera noltii

Abstract: Seagrass ecosystems are expected to benefit from the global increase in CO2 in the ocean because the photosynthetic rate of these plants may be Ci-limited at the current CO2 level. As well, it is expected that lower external pH will facilitate the nitrate uptake of seagrasses if nitrate is cotransported with H+ across the membrane as in terrestrial plants. Here, we investigate the effects of CO2 enrichment on both carbon and nitrogen metabolism of the seagrass Zostera noltii in a mesocosm experiment where plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 58 publications
6
47
1
Order By: Relevance
“…The short-term gas exchange measurements with CO 2 enrichment conditions clearly indicated that Z. noltei community production at around the same irradiance level increased 1.5-fold. Higher community production under CO 2 enrichment suggest that community production of Z. noltei are carbon limited under the current atmospheric CO 2 concentration, confirming the same conclusions previously obtained for Z. noltei (Alexandre et al, 2012) and for Z. marina (Beer and Koch, 1996;Zimmerman et al, 1997;Invers et al, 2001). These reports are on the photosynthetic response of individual plants rather than whole community, but it is expected that the increase in photosynthetic rate of individual plants is reflected on the higher organizational level of the community production.…”
Section: Co 2 Enrichmentsupporting
confidence: 87%
See 2 more Smart Citations
“…The short-term gas exchange measurements with CO 2 enrichment conditions clearly indicated that Z. noltei community production at around the same irradiance level increased 1.5-fold. Higher community production under CO 2 enrichment suggest that community production of Z. noltei are carbon limited under the current atmospheric CO 2 concentration, confirming the same conclusions previously obtained for Z. noltei (Alexandre et al, 2012) and for Z. marina (Beer and Koch, 1996;Zimmerman et al, 1997;Invers et al, 2001). These reports are on the photosynthetic response of individual plants rather than whole community, but it is expected that the increase in photosynthetic rate of individual plants is reflected on the higher organizational level of the community production.…”
Section: Co 2 Enrichmentsupporting
confidence: 87%
“…This was also observed in Z. marina (Zimmerman et al, 1997 and Z. noltei (Alexandre et al, 2012) where increase in CO 2 concentrations increased the light using capacity of individual plants.…”
Section: Par Responsessupporting
confidence: 61%
See 1 more Smart Citation
“…On the other hand, in a long-term experiment, there was no effect of increasing CO 2 levels on the aboveground productivity of Zostera marina (Palacios and Zimmerman, 2007), as opposed to belowground. Alexandre et al (2012) showed that the net photosynthetic rate of Zostera noltii was positively affected by the CO 2 enrichment of the seawater, but they did not observe an increase in leaf growth rates.…”
Section: Lauritano Et Al: Response Of Key Stress-related Genes Ofmentioning
confidence: 93%
“…Under such conditions, photosynthetic carbon assimilation is increased and photorespiration, which can reduce photosynthetic capacity of eelgrass by 40%, is decreased (e.g., Thom 1995;Zimmerman et al 1997;Palacios and Zimmerman 2007;Alexandre et al 2012;Buapet et al 2013). The most convincing evidence has been provided by Zimmerman and coworkers who have simulated coastal acidification in manipulative experiments with eelgrass for nearly two decades.…”
Section: Coastal Zone Acidificationmentioning
confidence: 99%